Analysis of some harmful behaviors against COVID-19 among the Cuban population - Gabriel Lajús Barrabeitg (Universidad de Ciencias Médicas de La Habana, 2020)
Introduction: Currently, the world is facing one of the most serious pandemics in history, the COVID-19. Objectives: To identify the main harmful behaviors among the Cuban population against the measures adopted to avoid COVID-19 contagion from December to May 2020. Material and Methods: An ordered systematic review was performed through searches for electronic articles indexed in national and foreign medical journals; official communications from international, regional, and national organizations; and newsletters published by some ministries during last five months in Havana, Cuba. Development: Similar harmful behaviors were found in Cuba and other countries since they are socially reprehensible and express different forms social indiscipline, antisocial behavior, and violations of the socially established order that can typify crimes.  However, in the island, they lack drama and do not go unpunished compared to other countries. Conclusions: The main harmful behaviors found were associated with the crime of spreading epidemics and the increase of social indiscipline and economic crimes  resulting from lack of demands, control, denunciation, social tolerance and decrease of revolutionary surveillance as an expression of a complex causal phenomenon which includes unsatisfied needs, economic and social issues, infodemic, communication distortion and low perception of risk. Some proper behaviors of the Cuban people such as as solidarity, altruism, kindness, humanism, spirituality, compassionate ability, and potential to get involved in the transmission of values, have also shown the inspiration of those people whose day-to-day commitment has contributed to the rich history of this country.